Considerations on the ex officio examination of jurisdiction in European family and succession Regulations - Melgarejo Cordón, Pablo M. (CUADERNOS DE DERECHO TRANSNACIONAL, 2023)
The purpose of this paper is to study the special features of ex officio monitoring of international competition in the material field of European family and succession Regulations. It also carried out an analysis of the STJUE of 7 April 2022, referring to the application of the provisions of Regulation 650/2012 in matters of succession, collecting some personal reflections and opinions in this regard.